Cyanine dyes in solid state organic heterojunction solar cells - Heier, Jakob; Peng, Chuyao; Vï¿½ron, Anna C.; Hany, Roland; Geiger, Thomas; Nï¿½esch, Frank A.; Vismara, Marcus V. G. [UNESP]; Graeff, Carlos F.O. [UNESP] (SPIE, the international society for optics and photonics, 2014)
Today numerous cyanine dyes that are soluble in organic solvents are available, driven by more than a century of research and development of the photographic industry. Several properties specific to cyanine dyes suggest that this material class can be of interest for organic solar cell applications. The main absorption wavelength can be tuned from the ultra-violet to the near-infrared. The unparalleled high absorption coefficients allow using very thin films for harvesting the solar photons. Furthermore, cyanines are cationic polymethine dyes, offering the possibility to modify the materials by defining the counteranion. We here show specifically how counterions can be utilized to tune the bulk morphology when blended with fullerenes. We compare the performance of bilayer heterojunction and bulk heterojunction solar cells for two different dyes absorbing in the visible and the nearinfrared. Light-induced Electron Spin Resonance (LESR) was used to study the charge transfers of light induced excitons between cyanine dyes and the archetype fullerene C60. LESR results show good correlation with the cell performance.
Keywords: Bulk heterojunction; C60; Counterion; Cyanine dyes; Light-induced electron spin resonance; Organic solar cells; PCBM; Solvent quench